Peran Quadruple Helix dalam Meningkatkan Kreativitas dan Kapabilitas Inovasi (Studi Pada Industri Kreatif Sektor Fashion) - Mulyana -; Sutapa - (Conference In Business, Accounting, And Management (CBAM), 2015)
Creative industries are significantly contribution to economic development, however the development of creative industries are still many problems, especially human resources, so it has an impact on the innovation capability. This study aims to examine the effect of quadruple helix (intellectual, government, business, civil soceity) to enhance the crativity and innovation capability, on sectors of fashion in Central Java. Sampling methods using purposive sampling and data analysis using the Partial Least Square (PLS). The research results that intellectual, government, business and civil soceity are significantly effect on the creativity. Intellectuals and business are significantly effect on the innovation capability, but government and civil soceity not significantly effect on innovation capability. Creativity is significantly effect on innovation capability Keywords: Quadruple helix, Creativity, Innovation Capability.